As relações entre desenho e escrita no processo de apropriação da linguagem escrita - Góes, Margarete Sacht (2014)
This work is constituted from studies carried out on the Education and languages research line belonging to the Program of Post-Graduation in Education held at the Espírito Santo Federal University. It uses a socio-historical approach for the qualitative investigation in the field of Human Sciences and aims at investigating the relations between drawing and writing elaborated by four-year old children going to a children’s educative institution. In order to analyze the data produced, it uses as basis, the theoretical assumptions from Mikhail Bakhtin, from the enunciatediscursive perspective, which language perspective helps understanding the drawing and writing on its discursive dimension as enunciation. Based on processes observed in the teaching-learning relations and in the verbal interaction among the research subjects, the work selects, for the first part of the study, teaching-learning situations experienced by the children and the Teacher in the activity room. In the second part of the analyses, it chooses the productions performed for the real and imaginary interlocutors and finalizes with the data analysis, inferring that the distinction between drawing and writing is a school construction, this way, it supports the thesis that different languages keep relations among them in the course of written language approach process and that such coexistence allows the expansion of the creative imagination, the production of singular and idiosyncratic marks within the texts produced by the children, besides providing a comprehension of how children are constituted in the world.